Map of Sustainable Agriculture Research Development: Global Bibliometric Analysis (2000–2025) - Loso Judijanto (West Science Agro, 2026)
This study maps the global development of sustainable agriculture research through a bibliometric analysis of publications indexed in Scopus from 2000 to 2025. Using VOSviewer for network visualization, the study examines publication trends, keyword co-occurrence patterns, and collaboration networks among authors, institutions, and countries. The findings reveal a substantial increase in research output over time, indicating growing scholarly and policy attention to sustainability in agriculture. Core research themes are strongly centered on sustainable development, climate change, food security, soil health, and environmental impact. The keyword network demonstrates a multidimensional structure in which environmental sustainability forms the conceptual backbone, supported by soil nutrient management and carbon-related studies. In addition, emerging clusters highlight increasing integration of biotechnology, microbial research, and digital technologies such as machine learning and smart agriculture. Country collaboration analysis identifies China as a dominant global hub, with strong linkages to Europe, North America, and other Asian regions, reflecting expanding international cooperation. Institutional networks further show the presence of key research centers that act as bridges in knowledge production. Overall, the study indicates that sustainable agriculture research is transitioning toward an integrated paradigm combining ecological resilience, technological innovation, and socio-economic sustainability. The results provide a comprehensive overview of the field’s evolution and offer insights into future research directions emphasizing interdisciplinary integration and global collaboration.